1986
DOI: 10.1192/bjp.148.2.120
|View full text |Cite
|
Sign up to set email alerts
|

II. A Randomised Controlled Trial of Prophylactic Neuroleptic Treatment

Abstract: Out of 253 patients fulfilling criteria for a first episode of schizophrenic illness, 120 entered a randomised placebo-controlled trial of maintenance neuroleptic medication on discharge; they were followed to relapse or loss to follow-up, for two years or to the end of the study. Of those on active medication, 46% relapsed, as did 62% of those on placebo; the most important determinant of relapse was duration of illness prior to starting neuroleptic medication. This finding might be because extended duration … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
133
2
3

Year Published

1986
1986
2006
2006

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 442 publications
(147 citation statements)
references
References 0 publications
9
133
2
3
Order By: Relevance
“…Evidence for a progressive deterioration has also been found in studies of first episode schizophrenia patients who were then followed prospectively from 1 to 5 years. [44][45][46] Those studies found that the length of time a person experienced psychotic symptoms in their first episode of illness, prior to receiving pharmacologic treatment, was a significant predictor of the time to treatment response, 44 relapse, 46 and long term outcome. 45 Specifically, the longer the duration of psychosis the poorer the treatment response and outcome.…”
Section: Sensitization and Schizophreniamentioning
confidence: 99%
“…Evidence for a progressive deterioration has also been found in studies of first episode schizophrenia patients who were then followed prospectively from 1 to 5 years. [44][45][46] Those studies found that the length of time a person experienced psychotic symptoms in their first episode of illness, prior to receiving pharmacologic treatment, was a significant predictor of the time to treatment response, 44 relapse, 46 and long term outcome. 45 Specifically, the longer the duration of psychosis the poorer the treatment response and outcome.…”
Section: Sensitization and Schizophreniamentioning
confidence: 99%
“…Although there has been very little study of factors that act to maintain recovery in remitted first-episode patients, evidence suggests that antipsychotics are highly effective in prevention of relapse (APA 2004). In patients for whom antipsychotics are prescribed, 1-year relapse risk varies from 0 to 46%, with relapse rates of patients who discontinue taking medication being up to five times higher than for those who continue treatment (e.g., Kane et al 1982;Crow et al 1986;McCreadie et al 1989;Robinson et al 1999b) (Level A ). The varying relapse rates found in these studies may be due to differences in the criteria used to define relapse, different study populations and different lengths of follow-up, and could in part be explained by different adherence to maintenance medication.…”
Section: Relapse Prevention In First Episode Patientsmentioning
confidence: 99%
“…In another study there were significantly fewer relapsed patients treated with flupenthixol decanoate (at least 40 mg/month i.m. ), chlorpromazine (at least 200 mg/day), haloperidol (at least 3 mg/day), pimozide (at least 4 mg/day) or trifluoperazine (at least 5 mg/day) compared to placebo over a period of 6Á/24 months (46 versus 62%) (Crow et al 1986). …”
Section: Relapse Prevention In First Episode Patientsmentioning
confidence: 99%
“…Firstepisode patients were, after a period of stabilization on antipsychotic medications, assigned to continue treatment with either antipsychotic medications or placebo (Crow et al, 1986). In both groups, patients who had been ill longer than 1 year at the time of their first hospital admission were more likely to relapse than patients who had been ill for less than a year; patients who received placebo substitution were more likely to relapse than patients who continued to receive antipsychotic medications.…”
Section: Evidence From Discontinuation Studiesmentioning
confidence: 99%